Influence of the rest time on carcass quality and pork meat characteristics - Jerez-Timaure, Nancy; Arenas de Moreno, Lilia; Sulbar?n, Mar?a; Uzc?tegui, Soj?n (Cuban Journal of Agricultural Science, 2013)
The influence of two rest times: long rest (20-22 h) and short rest (3-4 h) on carcass quality and pork meat characteristics was studied. Two hundred pigs (120 castrated males and 80 females) of similar genetic composition and age were evaluated. Animals were divided and sent to the slaughterhouse in groups of 50 pigs (two lots per treatment). pH and temperature at 45 min and 24 h after slaughtering (pH 45 min, pH 24 h, temp. 45 min., temp. 24 h) were measured. Also, the water holding capacity (WHC), dripping losses (DL), color, muscle profile, weight, length and carcass backfat, besides the defects (fractures, hemorrhages and contusions) in chop, shoulder and ham were calculated. The rest period did not affect (P = 0.6) pH 45 min, or the color. However, there were changes (P < 0.001) in the pH 24 and in the temperature at 45 min. and at 24 h, as well as in WHC and DL. Meat from animals with long rest time had higher pH 24 h value (5.80), lower DL (1.82%) and greater WHC (15.64%) regarding the values obtained in animals with short rest time (5.68, 3.44 % and 17.24 %, respectively). The highest meat frequency (73 %) with high pH 24 h (? 6.0) was produced with the long rest time, while with the short rest time was obtained 93 % of carcasses, with normal pH 24 h range (5.6- 5.9) with greater proportion of flawless chops and ham. Results demonstrate that with the short rest time the incidence of carcass quality problems (dark cut and flaws) related to mistakes in the animal welfare decreased. Key words: quality, meat, pigs, animal welfare, pH, rest time